A Syntax-Based Analysis Of Predication: Linguistic Structures - Nadhira Afifah; Nur Ain Nun; Mutia Zahra; Siti Ismahani (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This article reviews a syntax-based analysis of predication in language, delving into its underlying linguistic structure. The research conducted employs analytical methods sourced from literature to comprehend sentence construction and the syntactic relationships forming predication. The findings of the analysis present a profound understanding of the framework of predication in language and its implications in human communication. In the exploration of syntax and predication in linguistics, the syntactic approach highlights the essential relationship between subject and predicate in a sentence. Predication maps what is stated about the subject, and syntax-based analysis reveals its basic structure. Syntax, with its central role, is key to understanding sentence structure and the meaning conveyed in communication. Research on this concept shows how the arrangement of words, phrases, and clauses forms predication.